ANALISIS POTENSI SWADAYA MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI DESA BAKIDA, KECAMATAN HELUMO KABUPATEN BOLAANG MONGONDOW SELATAN - Perlin Kuku; Djamila Podungge; Nuzmerini Rauf (Journal of Economic, Business, and Administration (JEBA), 2024)
This internship was carried out with the aim of knowing and analyzing community self-help in development planning in Bakida Village, Helumo District, South Bolaang Mongondow Regency. This research uses qualitative methods so that it can provide an understanding of a phenomenon by using data collection techniques carried out using observation techniques, interviews and documents. The results showed that the potential for self-help in development planning in bakid a village,Helumo District, South Bolaang Mongondow Regency has been running well but thereare several focuses that need improvement, including quality in development planning in Bakida village.